Dancing to the tune of democracy: Agents negotiating power to decentralise water management - Saravanan V. Subramanian (University of Bonn, Center for Development Research (ZEF), 2009)
The current debate on decentralisation offers a partial and polarised view on the sharing of power to manage water. Drawing New Institutionalism as applied in the social and ecological sciences, the paper argues that decentralisation represents a complex adaptive process, wherein agents draw upon the activities of multiple actors and their rules to negotiate and renegotiate their unequal power relations. Examining a watershed in the Indian Himalayas as a case study, the paper demonstrates the incremental and cumulative integration of statutory and socially-embedded rules in facilitating the agents' negotiation process. It reveals the cunning and adaptive behaviour of the agents to decentralise water resource management. The paper argues that though the contemporary decentralised reforms offered opportunities for these agents to negotiate, they do not ensure resource use efficiency, equity, accountability and participation of stakeholders in management of water. The paper identifies the significance of authority, information, scope and pay-off rules to facilitate decentralisation reforms. It recommends the conventional state-centric regulation to strengthen these rules for more informed management of water resources.
urn:nbn:de:101:1-20090923111
Keywords: 330; institutional analysis; agents; institutional change; power dynamics; Asia; India